HUBUNGAN ACTIVITY DAILY LIVING TERHADAP KUALITAS HIDUP PASIEN KANKER YANG MENALANI KEMOTERAPI DI RSUP FATMAWATI - Selvy Juwita Sari (2020)
Cancer is an oncological malignancy that occurs due to cell division continuously and uncontrolled. Chemotherapy is currently one of the important cancer treatments, considering that cancer is the cause of death in several countries. One of the effects of chemotherapy is the decrease in patient's daily living activity which affects the quality of life of patients. This study aims to analyze the relationship between daily living activity and the quality of life of cancer patients. This study uses a correlational design with a cross sectional approach to 63 respondents using a purposive sampling method. The data taken is obtained from primary data using a questionnaire. Analysis of the data in this study used the Spearman correlation test. The results of this study indicate there is a relationship between daily living activity on the quality of life of cancer patients with daily living activity with the results (p value = 0.014). The researcher suggests that this research can be continued by adding other variables.